PENGARUH KEBIJAKAN DIVIDEN, RETURN ON ASSET DAN RETURN ON EQUITY TERHADAP RETURN SAHAM - Wiwi Widya Ningsih; Novera Kristanti Maharani (PAPATUNG: Jurnal Ilmu Administrasi Publik, Pemerintahan dan Politik, 2022)
This study aims to determine the effect of dividend policy and profitability on stock returns in the Consumer Goods industry company simultaneously and partially. This method uses quantitative methods, the analytical technique used is descriptive statistics, while hypothesis testing uses multiple linear regression analysis. The determination of the sample was carried out using the purposive sampling method in the Consumer Goods industry company for the 2016-2020 period. The results of this study indicate that simultaneously dividend policy, return on assets and return on equity have an effect on stock returns. Partially, only the dividend payout ratio has an effect on stock returns. Return on assets and return on equity partially have no effect on stock returns.